REB/VODKA IS MY OTP: SCHOOL SHOOTER AND MASS MURDERER FANFICTION AS NARRATIVES OF RESISTANCE - Jones, Bethan Victoria (AoIR Selected Papers of Internet Research, 2023)
Early work in fan studies deliberately focused on the positive aspects of fandom. This approach was designed to combat the stereotyping and pathologizing of fans perpetrated by mass media (Jenson, 1992; Zubernis and Larsen, 2012) and has broadly been successful. Yet popular culture is a site of political meaning and ideological conflict and recent shifts point toa pressing need to understand the dominant narratives being espoused. Work in fan studies is now being carried out on white supremacy, conspiracy theories and serial killer fandom (Stanfill, 2020; Reinhard et al., 2021; Wiest, 2016), but communities rising around people like Eric Harris and Dylan Klebold and Dzhokhar Tsarnaev remain unexplored.This paper returns to some of the early discourses surrounding fandom and applies them to contemporary expressions of ‘dark’ fandom, in particular school shooters and mass killers. Using surveys and undertaking a content analysis of fanfiction posted to Archive of Our Own, as well as media reports focusing on these fans, I demonstrate that some forms of fandom and fan behaviour are still dismissed and Othered. Typically stigmatised through its gendered associations, fanfiction dedicated to mass killers is subject to multiple discourses of othering, but also offers multiple forms of resistance to these dominant narratives. Rather than fanfiction as a practice through which fans express emotional connections with popular media texts, I argue that fans write fanfiction about school shooters and mass killers as a way to recontextualize and understand their motives and actions in ways that other media do not.